Hydroxysafflor yellow A attenuates sepsis-induced intestinal barrier dysfunction by modulating Bcl-2/SOD2-mediated mitochondrial apoptosis - Fei, Jinzhong; Xu, Chencheng; Chen, Chaochao; Chen, Qing; Wu, Zhengbin; Wang, Yaoli; Bao, Daiqin; Shao, Shifeng (Frontiers in Pharmacology, 2026)
BackgroundSepsis remains a major cause of hospital mortality. Sepsis-induced intestinal injury is regarded as the driving force behind the rapid progression of critical conditions such as shock and sepsis, and serves as the initiating factor of subsequent organ dysfunction. Therefore, the development of effective therapeutic agents to restore intestinal barrier function is crucial for improving outcomes in sepsis.MethodsA caecal ligation and puncture (CLP) model was established in mice to induce sepsis, and intestinal epithelial cells (IEC-6) were treated with lipopolysaccharide (LPS) to simulate sepsis in vitro. These models were used to investigate the protective efficacy and molecular mechanisms of hydroxysafflor yellow A (HSYA) against sepsis-induced intestinal barrier dysfunction.ResultsHSYA alleviated intestinal barrier dysfunction in septic mice, markedly reduced levels of inflammatory factors, and improved survival. In vitro, HSYA enhanced barrier function of IECs, reduced mitochondrial fragmentation and reactive oxygen species (ROS) accumulation, promoted proliferation and inhibited apoptosis by upregulating the expression of Bcl-2 and SOD2.ConclusionThe study demonstrated the therapeutic potential and underlying mechanisms of HSYA in ameliorating sepsis-induced intestinal barrier injury, providing a new strategy for sepsis treatment.